1963
DOI: 10.1107/s0365110x63000967
|View full text |Cite
|
Sign up to set email alerts
|

Neutron diffraction study of magnesium deuteride

Abstract: A magnesium deuteride preparation of composition Mg(D0.gH0.1) 2 is found to be tetragonal with a=4.5025, c=3.0123/~. The atomic positions are:2 Mg in (000) ~922/ , 1~1-~ 4(D +H) in _+ (xxO) (½ +x, t-x, 1) with x =0.306 _+0"003.The bond lengths are Mg-6D = 1.95 + 0.02 A. The structure is of the rutile type, Some years ago it was shown by X-ray diffraction (Ellinger et al., 1955) that magnesium hydride is tetragonal with two molecules in a unit cell of dimensions a--4.5618_+ 0.0005, c=3.0205_+ 0.0005 A.The two m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(53 citation statements)
references
References 1 publication
5
47
0
1
Order By: Relevance
“…A study of GGA in VASP using many metal-hydrides, including MgH 2 , showed that this choice of exchange-correlation yields results that compare well to experimental formation enthalpies. 25 The bulk lattice parameters and formation energy (including zeropoint (ZP) energy) for rutile MgH 2 calculated in DFT-PW91, see Table 1, are in very good agreement with experiment 26,27 and other DFT 23, 28 and quantum Monte Carlo 29,30 (which, in principle, are exact) calculations. For structural energy differences at fixed stoichiometry, e.g., from relaxation or configurational changes, the effects of ZP energy effectively cancel.…”
Section: Computational Detailssupporting
confidence: 60%
“…A study of GGA in VASP using many metal-hydrides, including MgH 2 , showed that this choice of exchange-correlation yields results that compare well to experimental formation enthalpies. 25 The bulk lattice parameters and formation energy (including zeropoint (ZP) energy) for rutile MgH 2 calculated in DFT-PW91, see Table 1, are in very good agreement with experiment 26,27 and other DFT 23, 28 and quantum Monte Carlo 29,30 (which, in principle, are exact) calculations. For structural energy differences at fixed stoichiometry, e.g., from relaxation or configurational changes, the effects of ZP energy effectively cancel.…”
Section: Computational Detailssupporting
confidence: 60%
“…In contrast to the completely homogeneous nature of this reaction solution, a further NMR-scale experiment between [(Mg{N(SiMe 3 ) 2 } 2 )] and two molar equivalents of PhSiH 3 deposited a gelatinous precipitate, presumed to be polymeric MgH 2 , in a matter of minutes. The sole soluble product from this reaction was PhH 2 SiN(SiMe 3 ) 2 , which provided 1 H NMR chemical shift data identical to the silane product observed in the initial reaction of 1 and PhSiH 3 .…”
mentioning
confidence: 60%
“…[1,2] This simple binary compound is more commonly encountered, however, as a typical ionic solid and in the condensed phase both tetragonal (rutile, a-MgH 2 ) and high-pressure orthorhombic (g-MgH 2 ) modifications have been identified by X-ray and neutron diffraction experiments respectively. [3,4] Although a weight % of 7.6 % of hydrogen has recently reinvigorated interest in MgH 2 as a potential solid-state hydrogen-storage medium, [5] there are no reports of well-defined and tractable molecular magnesium hydrides with H:Mg ratios greater than 1. While a variety of heteroleptic magnesium hydride species, XMgH (X = halide, alkyl, aryl, cyclopentadienyl, alkoxo, amido) have been known for some time, and have been shown to have some use in effecting reductive transformations, their structures are incompletely defined and, most likely, poly-or oligomeric.…”
mentioning
confidence: 99%
“…STRUCTURAL ASPECTS α-MgH 2 crystallizes in the rutile-type structure (P42/mnm) at ambient conditions. 28,29 At higher temperatures and pressures, α-MgH 2 transforms into the orthorhombic γ-MgH 2 modification (α-PbO 2 ; Pbcn). It should also be noted that Bortz et al investigated the crystal structure of γ-MgH 2 from powder neutron-diffraction data collected at 2 GPa.…”
Section: Computational Detailsmentioning
confidence: 99%